Construction of the Parenting Skills Scale, in both Parents - Martínez Guadarrama, Gustavo (Consorcio de Universidades Mexicanas A.C., 2014)
The objective of this research was to construct a valid and reliable scale to measure parenting skills in parents. We worked with 341 men and 341 women from Toluca city whose children were between 6-12 years of age. The skills relied on: educational, parental agency, autonomy and social support, personal life and relationship, and domestic organization (Rodrigo & Máiquez, 2008). The procedure carried out was: first to submit to judges’ preliminary instrument validity, then a pilot was conducted and finally, the application of the instrument collectively. The information processing is carried out for validity using exploratory factor analysis of orthogonal type with varimax rotation and reliability Cronbach’s alpha. According to the results, eight dimensions were obtained by the men’s instrument and five dimensions were obtained by the women’s instrument. In both, parents affection, partner agreements, cleaning and security, stimulation and development and parental self-efficacy skills were found. Male parents showed three more: affection, problem solving and adaptation to the characteristics of the child. Both scales are valid and reliable, so that it is concluded that both parents considered important all everyday parenting skills which are essential for the biopsychosocial development of children.